The Role of Brand Loyalty: The Case Study of Telekom Malaysia - Husain, Munawwer (International Review of Management and Marketing, 2015)
Brand devotion is the principal thing in an association that leads from consumer loyalty toward items and administrations offer. This study is led to investigate the principle calculates that add to brand dedication in the telecom organization, TM .There are five primary variables utilized as a part of the contextual investigation that is duty, consumer loyalty, corporate picture, trust and advancement on brand devotion in the telecom organization. This study utilized overview systems, where a sum of 290 review structures was circulated to TM clients through comfort examining yet just 165 were gotten and usable. The outcome demonstrates a critical positive relationship between the variables (duty, consumer loyalty, corporate picture, trust and advancement) toward brand dedication. Keywords: Brand; Commitment; Customer satisfaction; Trust; Promotion JEL Classifications: L80; M31; M37